84.7k views
4 votes
Which expression is equivalent to sqrt 900f^6/100g^4

User HAVB
by
5.3k points

2 Answers

2 votes

Answer:

3f³/g²

Explanation:

√(900f^6/100g^4) =√(9f^6/g^4)=3f³/g²

User Davinder Goel
by
4.6k points
1 vote

Answer:


[3f^(3)g^(-2)]

Explanation:

The given expression is
\sqrt{(900f^(6) )/(100g^(4))}

We can rewrite the expression as
\sqrt{((30f^(3))^(2))/((10g^(2))^(2))}

Now we can remove the radical of the expression =
(30f^(3) )/(10g^(2) )

=
[(3f^(3) )/(g^(2))]

=
[3f^(3)g^(-2)]

=
[3f^(3)g^(-2)] is the answer.

User Jorge Rocha
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.